ANAEMIA DURING PREGNANCY: AN INTEGRATED REVIEW OF THREATS, IMPACTS, AND TREATMENT APPROACHES - Dewi Hestiani K; Ulfa Sufyaningsi; Andi Suriyani (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Maternal anaemia, a condition in which haemoglobin levels drop during pregnancy, is a serious health problem especially in developing countries. The CDC identifies anaemia as haemoglobin levels below 11 gr/dl in the first trimester and less than 10.5 gr/dl in the second trimester, causing symptoms such as excessive fatigue, pale skin, and rapid heartbeat. Risk factors include young age, low education, low socioeconomic status, and deficiencies in micro-nutrients such as iron, vitamin B12 and folate. Anaemia in pregnancy risks prematurity, insufficient iron stores in the newborn, and even perinatal death. This study used a systematic approach in collecting relevant literature, emphasising the importance of a holistic approach in the management of maternal anaemia, including knowledge improvement, nutritional supplementation, and socioeconomic support. Results show that deficiencies in iron, other nutrients and pre-pregnancy factors play an important role in anaemia risk. With a global prevalence of 29.9% in women of reproductive age, this study calls for more effective and innovative intervention strategies to address maternal anaemia, including oral iron therapy, treatment of comorbidities and health education. In conclusion, maternal anaemia requires an integrated approach involving health services, family support and cultural adaptation to improve adherence and well-being of pregnant women and fetuses.